2002
DOI: 10.1038/ncb808
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A-interacting protein (FILIP) regulates cortical cell migration out of the ventricular zone

Abstract: Precisely regulated radial migration out of the ventricular zone is essential for corticogenesis. Here, we identify a mechanism that can tether ventricular zone cells in situ. FILIP interacts with Filamin A, an indispensable actin-binding protein that is required for cell motility, and induces its degradation in COS-7 cells. Degradation of Filamin A is identified in the cortical ventricular zone, where filip mRNA is localized. Furthermore, most ventricular zone cells that overexpress FILIP fail to migrate in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 29 publications
4
119
0
1
Order By: Relevance
“…Several in utero experiments have revealed a role for LIS1 , DCX (Bai et al, 2003), CDK5 (Ohshima et al, 2007), and Filamin A (Flna) (Nagano et al, 2002(Nagano et al, , 2004 in the regulation of the multipolar stage. Here, we have shown two means to rescue neurons stalled in the multipolar stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several in utero experiments have revealed a role for LIS1 , DCX (Bai et al, 2003), CDK5 (Ohshima et al, 2007), and Filamin A (Flna) (Nagano et al, 2002(Nagano et al, , 2004 in the regulation of the multipolar stage. Here, we have shown two means to rescue neurons stalled in the multipolar stage.…”
Section: Discussionmentioning
confidence: 99%
“…FLNa interacting protein (FILIP), ribosomal S6 kinase, protein kinase C␣, and GTPases of the Rho-and Rac-families, which thereby implicate FLNa in cell shape modulation and integrindependent adhesion and motility (Nagano et al, 2002;Ohta et al, 1999;Tigges et al, 2003;Woo et al, 2004). GTPases have the extraordinary ability to remodel actin-based cytoskeletal structures.…”
Section: Discussionmentioning
confidence: 99%
“…This was further supported by indications that FLNa-deficiency impaired neuronal migration (Fox and Walsh, 1999;Nagano et al, 2002). Further studies based on knockout mice (Hart et al, 2006;Feng et al, 2006) and the use of small interference RNA showed that while in many settings loss of only one FLN isoform is not sufficient to impair migration, loss of two or more FLNs impaired initiation of migration and cell spreading Lynch et al, 2011;Heuzé et al, 2008).…”
Section: Introductionmentioning
confidence: 89%